Analysis of Teachers' Digital Pedagogical Competence in Creating Innovative and Creative Learning at Elementary School - Nafasabilla, Zaskia; Yohamintin, Yohamintin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study aims to analyze teachers’ digital pedagogical competence in creating creative and innovative learning at Mutiara Hikmah Al-Qur'an Elementary School. The background of this study is based on the need to improve teachers' competence in integrating digital technology in the 21st-century education era. The study used a qualitative approach with a case study method, where data were collected through observation, interviews, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results showed that teachers at Mutiara Hikmah Elementary School have understood and interpreted the importance of digital pedagogical competence, both through internal training and independent development. Teachers are able to innovate by utilizing various digital technology platforms and implementing creative learning models such as project-based learning and game-based learning, thereby creating a creative, innovative, interactive, and student-centered learning environment. These efforts encourage the improvement of students' creativity, critical thinking, communication, and collaboration skills. Sufficient technological facilities and teachers' initiatives in developing digital pedagogical competencies also contribute to the creation of creative, innovative, and relevant learning that meets the demands of the digital age.